The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/uog.10139
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester diagnosis of cleft lip and palate using three‐dimensional ultrasound

Abstract: Objective To determine whether systematic examination of primary and secondary palates using three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 21 publications
1
96
1
2
Order By: Relevance
“…In fact, the detection rate for any fetal structural malformation in the first trimester only reaches a value in the range 0.7−4.7% [24]. Reports of CP in the first trimester are scarce [10,][11,26,27,28]. Syngelaki et al [25] demonstrated a 5% detection rate for facial cleft with non-chromosomal abnormalities at 11-13 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the detection rate for any fetal structural malformation in the first trimester only reaches a value in the range 0.7−4.7% [24]. Reports of CP in the first trimester are scarce [10,][11,26,27,28]. Syngelaki et al [25] demonstrated a 5% detection rate for facial cleft with non-chromosomal abnormalities at 11-13 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-ten et al [11] used the multiplanar mode display to visualize all cases of clefting of the primary palate and 86% of cases involving the secondary palate in 237 women undergoing first-trimester ultrasound screening for aneuploidy using 3D ultrasound. Ghi et al [29] diagnosed one case of bilateral CLP by 2D ultrasound combined with 3D surface imaging at 12 weeks, and proposed that 3D techniques can provide more information for diagnosis of CLP than 2D ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mailáth-Pokorny et al (2010) investigated the role of foetal MRI in the antenatal diagnosis of facial clefts, including cleft lip, although no particular detection technique has been employed. Martinez-Ten et al (2012) investigated whether systematic examination of primary and secondary palate supported the detection of face cleftings during first trimester. Gindes et al (2013) studied the potential of three-dimensional US for palate view in foetuses at high risk for CLP.…”
Section: Introductionmentioning
confidence: 99%
“…Facial landmarks were here cited as identifiers for various face parts (Sepulveda et al, 2012a). Finally, they determined whether systematic examination of primary and secondary palates aided in the identification of orofacial clefts in the first trimester (Martinez-Ten et al, 2012). They also reviewed techniques, advantages, limitations, and clinical applications of 3D ultrasound and fetal MRI (Sepulveda et al, 2012b) and pointed out that anatomical landmarks had a key role in assessing fetus's normal structure (Sepulveda et al, 2012c).…”
Section: Introductionmentioning
confidence: 99%